2015
DOI: 10.1016/j.foodres.2014.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the loss and emergence of volatile compounds during the concentration of cashew apple juice (Anacardium occidentale L.) and the impact on juice sensory quality

Abstract: Concentrating cashew apple juice alters the beverage aroma and flavor, compromising consumer acceptability of the concentrated beverage. To understand the mechanisms involved in these changes, this research characterized the dynamics of the loss and emergence of volatile compounds during cashew apple juice concentration, reporting their impact on beverage sensory quality. Fresh cashew apple juice (10.3°Brix) was concentrated in a thermal-siphon type evaporator operating in a closed system. Five samples were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
3
11
0
1
Order By: Relevance
“…On the other hand, sensor W1W, highly developed in AJD, reacted on many terpenes, organic sulfides, and inorganic sulfide (H2S), which were poor in ADJ. These were the same findings as Biasto et al [ 60 ], who concluded that high °Brix content apple juice was reduced in terpenes. W1C, W1S, W2S, W6S, and W5S were greatly developed in AJD.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, sensor W1W, highly developed in AJD, reacted on many terpenes, organic sulfides, and inorganic sulfide (H2S), which were poor in ADJ. These were the same findings as Biasto et al [ 60 ], who concluded that high °Brix content apple juice was reduced in terpenes. W1C, W1S, W2S, W6S, and W5S were greatly developed in AJD.…”
Section: Discussionsupporting
confidence: 90%
“…Among the samples analyzed, the ones that underwent thermal treatment presented lower amounts of compounds, being this factor due to the process of pasteurization, that brought about a decrease in the number of compounds resulting from the heating effect and the consequent volatilization of some highly volatile compounds. The reduction in the number of identified terpenes and even in some cases the increase in specific terpenes, such as β-pinene, can be explained by the fact that the thermal processing, under acidic conditions, can cause the conversion of the terpenes to other terpenes, however, many of these compounds cannot be detected in the chromatographic run because of their low volatility, as reported by Biasoto et al (2015). In summary, an explanation for the reduction or increase of the terpenes in the thermally treated mango pulp would be due to the sensitivity of these compounds, which may degrade to other compounds during thermal processing, depending on their polarity.…”
Section: Volatiles Profilementioning
confidence: 76%
“…(2007) during the processing of apple juice concentrate. On the other hand, an increase in ketones and alcohols was observed in processed apple juice according to multiple studies ( Schmutzer et al., 2014 ; Biasoto et al., 2015 ). Su and Wiley (2006) .…”
Section: Introductionmentioning
confidence: 96%
“…In addition, there is a loss of about 33.3-59.9% in ethyl 2-methyl butyrate and 55.3-75.4% in hexanal as reported by Komthong et al (2007) during the processing of apple juice concentrate. On the other hand, an increase in ketones and alcohols was observed in processed apple juice according to multiple studies (Schmutzer et al, 2014;Biasoto et al, 2015). Su and Wiley (2006).…”
Section: Introductionmentioning
confidence: 97%